METODE PEMBUKTIAN KESAHIHAN HADIS - Usman Usman (Widyariset, 2009)
Everyone who will convey Tradition of The Prophet (hadits) must check his integrity so that not everybody can convey hadits. Appearance fake haditses push hadits experts to specify a method for proving hadits authenticity, by checking sanad (the transmission of hadits) and matan (text of hadits). Sanad and matan are two fundamental elements on every Hadits. There is a very tightly bearing that cannot be disassociated between sanad and matan. One  saying can be called as Hadits, if founded the existence of transmission of rawi (transmitterr) which waschronically up to the first source (Prophet Muhamad). On the contrary, the network of carriers, though to Prophet, without existence of message (text) which informed can not be called as Hadits. Existence of method for proving hadits authenticity is expected to become reference for everyone wishing to convey hadits correctly.